RELATIONSHIP OF FUNCTIONAL STATUS OF PERSONS HAVING CHRONIC ‘NON-AFFECTIVE PSYCHOSIS’ WITH ANXIETY, DEPRESSION AND SELF-ESTEEM OF FAMILY CAREGIVERS - Jyothis P Soly; Sandhya Gupta; Mamta Sood (Indian Journal of Psychiatric Nursing)
Family caregivers who provide care to the individuals with chronic disabling mental disorder are themselves at risk of developing physical and psychiatric symptoms due to constant demands on their energy and time. The physical strains of caring of someone who may not perform activities of daily living can have detrimental effects on psychological health of family caregiver. A cross sectional study was conducted on sample of 60 patients with chronic non-affective psychosis, currently in remission and their 60 family caregivers from the selected setting were included WHO Disability Assessment Schedule, for patients, Hamilton Anxiety Scale, Quick Inventory of Depressive Symptomatology Self Report 16 and Rosenberg Self-Esteem Scale for family caregivers were used to accomplish the aim of the study. The study revealed patients had highest level of functional disability in the domain of participation and lowest level was in the domain of mobility. Family caregivers were anxious and depressed. Self-esteem of family caregivers was found to be low in some of the caregivers. Functional disability of patients had statistically significant positive correlation with levels of anxiety of family caregivers and their levels of depression whereas significant negative correlation was found with levels of self-esteem of family caregivers. The study concludes that measures to deal with functional disability of persons with chronic non-affective psychosis is to be taken and the caregivers also need to be assessed for their mental health needs.